Comorbid Depression is Associated with Increased Major Adverse Limb Events in Peripheral Arterial Disease: A Systematic Review and Meta-analysis. (July 2022) - Abi-Jaoudé, Joanne G.; Naiem, Ahmed A.; Edwards, Thomas; Lukaszewski, Marie-Amélie; Obrand, Daniel I.; Steinmetz, Oren K.; Bayne, Jason P.; MacKenzie, Kent S.; Gill, Heather L.; Girsowicz, Elie
Abstract : Objective: Depression is a significant risk factor for death in coronary artery disease. Conversely, the research surrounding depression and peripheral arterial disease is limited. This review aimed to systematically evaluate the available literature on the impact of comorbid depression on adverse outcomes in peripheral arterial disease. Data sources: A systematic review and meta-analysis were performed using the following databases MEDLINE, EMBASE, CINAHL, PsycINFO, and Cochrane Library from inception until July 2021. Review methods: Included studies compared depressed and non-depressed patients with peripheral arterial disease. The outcomes included death, major adverse cardiovascular events, and major adverse limb events. Results: A total of 9 297 articles were searched. Of these, seven studies were identified. Depressed patients were more likely to be women, diabetic, have a history of smoking, and have chronic limb threatening ischaemia, despite being younger than non-depressed patients. There was a 20% increase in major adverse limb events in depressed patients (RR 1.20, 95% CI 1.11 – 1.31, z = 3.9, p < .001, GRADE strength: very low) but no increased risk of death (RR 1.03, 95% CI 0.72 – 1.40, z = 0.06, p = .95, GRADE strength: very low) or major adverse cardiovascular events (RR 1.16, 95% CI 0.67 – 2.01, z = 0.54, p = .59, GRADE strength: very low). A follow up meta-regression of various comorbidities and demographic variables did not demonstrate a significant contribution to the observed risk ratio for major adverse limb events. Conclusion: Depression was reported in 13% of patients with peripheral arterial disease, associated with more medical comorbidity, and a 20% increased risk of major adverse limb events. Although the strength of this evidence is very low, the current state of the literature remains limited. Future studies should prospectively assess the impact of depression and its relationship to medical comorbidities and high risk health behaviours.